Axillary Impella insertion under regional nerve block: A case report. Issue 4 (22nd June 2019) - Raghunathan, Deepa; Hernandez, Nadia; Rajagopal, Keshava; Jumean, Marwan
Abstract: Percutaneous coronary interventions with the Impella (Abiomed, MA) catheter‐based, micro‐axial mechanical left ventricular assist device is a safe option for patients undergoing higher risk interventions. However, severe peripheral arterial disease limits vascular access for Impella insertion. Upper extremity arterial access has been traditionally obtained under general anesthesia. We present the first case, to our knowledge, of using peripheral nerve blocks for Impella 3.5 CP insertion into the axillary artery.